2021
DOI: 10.1139/cjfas-2020-0030
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of pop-up satellite archival tags on the swimming performance and behavior of young-adult mahi-mahi (Coryphaena hippurus)

Abstract: Pop-up satellite archival tags (PSATs) have been used to demonstrate habitat utilization and large-scale migrations of aquatic species and are a critical tool to manage highly migratory fish populations. Use of PSATs has increased in recent years; however, few studies have investigated the physiological and behavioral effects of carrying a PSAT. To address this gap, young-adult mahi-mahi (Coryphaena hippurus; 25–35 cm fork length) were tagged with miniature PSATs and assessed in a two-part experiment utilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Finally, increased mortality over the first 8 days cannot be attributed to tagging with PSATs since experiments on captive mahi-mahi found no effect on survival, feeding success, distance swam, acceleration, or velocity. 57 Given the higher rate of predation on oil-exposed fish in the first 8 days, alterations in depth and activity relative to control fish likely made oil-exposed mahi-mahi more vulnerable to predators.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, increased mortality over the first 8 days cannot be attributed to tagging with PSATs since experiments on captive mahi-mahi found no effect on survival, feeding success, distance swam, acceleration, or velocity. 57 Given the higher rate of predation on oil-exposed fish in the first 8 days, alterations in depth and activity relative to control fish likely made oil-exposed mahi-mahi more vulnerable to predators.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other studies of tagged tuna captured by rod and reel also indicate that tagging itself does not result in high levels of mortality (e.g. Lam et al 2020Tolotti et al 2020, and lab studies also showed no survival or behavioural impacts of satellite tagged, captive mahimahi (Coryphaena hippurus) compared to untagged conspecifics (McGuigan et al 2021). It appears that the commercial longline hauling is more responsible for the high mortality we have observed, rather than the satellite tagging procedure itself.…”
Section: Discussionmentioning
confidence: 96%
“…Although PSATs have advanced our understanding of the movements of many such migrants, the relatively large size of the first‐generation PSATs has largely prevented their use on many smaller fishes. Recent advances in PSAT technology have led to miniaturization of tags that permits their use on a wider range of fishes (Amilhat et al ., 2016; Graves et al ., 2009; McGuigan et al ., 2021; O'Neill et al ., 2018), but studies in which these tags have been used to track smaller fishes (30–50 cm) remain sparse. Long‐term attachment of satellite tags to smaller fishes has often been problematic.…”
Section: Introductionmentioning
confidence: 99%